Resilience Level and Associated Factors Among Medical Undergraduates in a Selected University in Sri Lanka - Manori, Shamila; Bowatta, Sanjeewa (Asian Journal of Interdisciplinary Research, 2024)
Medical undergraduates experience many challenges in their academic, social as well as financial aspects in present day circumstances. All these challenges make them vulnerable if they can’t withstand it. Resilience is the ability to withstand adversities an individual faces. If they lack resilience, they are likely to face many negative consequences. Objective of the study was to assess the resilience level and associated factors among medical undergraduates in a selected university in Sri Lanka. A descriptive cross-sectional study was conducted among all the medical undergraduates (n= 578) studying in the medical faculty during April to September 2023 in Wayamba medical faculty. Study instruments consist of the 14-Item Resilience Scale, to assess the level of resilience and a self-administered questionnaire to inquire the associated factors. The levels of resilience were expressed as percentages with 95% CI. Bivariate and multivariate logistic regression is used to assess the associated factors of low resilience. Probability < 0.05 was selected as the significance level. The results were expressed as odds ratios (OR) and 95% CI. The response rate was 85.3% (n= 492). Mean age was 22 years (SD =1.2) and majority were females (69.3%). Low, moderate, and high levels of resilience of medical undergraduates were 51% (n = 251), 30% (n = 148) and 18.9% (n =93) respectively. In each academic year, half of the undergraduates had low level of resilience. Male sex (AOR = 2.4; 95% CI =1.2 – 4.8), getting angry frequently (AOR = 3.0; 95% CI = 1.5 -6.0) and not engage in extracurricular activities (AOR = 2.2; 95% CI = 1.2 - 4.2) were significantly associated with low resilience level among medical undergraduates. Except the sex, other two are modifiable factors and need to take necessary interventions to rectify it. Recommend resilience enhancing interventions among medical undergraduates. Needs to explore the research area with qualitative studies to get highest yield.